Analisa Perbandingan Squid 2.7, Squid3, Dan Squid Lusca Sebagai Cache Proxy Server Pada Ubuntu Server - Gilang Ferdiansyah; Kustanto Kustanto; Sri Hariyati Fitriasih (STMIK Sinar Nusantara, 2021)
RT/RW Net Joho Baru is one of the internet service provider organizations. As one of the growing internet service provider RT/RW Net Joho Baru has to give the best and the quickest services to the customers. So that it need appropriate technology which is support to the best networks to give good services to the customers. The Important factors are cost and speed factors which related to the material efficiency and time. This research is comparing about proxy server operating systems such as Squid 2.7, Squid3, and Squid Lusca, so that it can easier to find out the appropriate operating systems to build the best network. SDLC Method has several steps. The first step is the analysis of feasibility study which included software and hardware. The second step is the analysis of needs which is planning relate to the system project. Then network planning design is going apply. Next, continuing design system to system testing. Based on these steps, the proxy server is successfully to shorten time management on accessing the website. The results of the efficiency acquisition are Squid 2.7 at 75,1%, Squid3 at 83,5%, and Squid Lusca at 86,9%.